Idiopathic Thrombocytopenia with Iron Deficiency Anemia. Issue 6 (January 2013) - Ibrahim, Ramy; Alhilli, Jaffar Ahmad; Cooper, Tyler T.; Dashkova, Irina; Guy, Judah; Gandhi, Anjula; Zaman, Mohammad
We report a rare case of anemia and thrombocytopenia as a result of uterine fibroid and adenomyosis, complicated by immune thrombocytopenic purpura (ITP). Symptoms were presented as menorrhagia and metrorrhagia in a 34-year-old African American woman, who was later treated with blood and platelet transfusion and iron therapy with steroids. Uterine fibroids are commonly found to cause hematologic disturbances such as anemia and reactive thrombocytosis and, less commonly, thrombocytopenia. Moreover, such hematologic disturbances are secondary to heavy and irregular uterine bleeding, which is typically presented. A previous uterine fibroid diagnosis was made and reconfirmed by pelvic and transvaginal ultrasound to exclude other locoregional pathologies. ITP was suggested by Coombs test and several other serologies, leading to confirmation via bone marrow biopsy. In a previous case study, we reported positive responses in hemotecrit and platelet count after the introduction of iron therapy to an iron-depleted middle-aged female presenting severe anemia and thrombocytopenia. 1